2016
DOI: 10.1016/j.neurobiolaging.2016.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Age increases reactive oxygen species production in macrophages and potentiates oxidative damage after spinal cord injury

Abstract: Age potentiates neurodegeneration and impairs recovery from spinal cord injury (SCI). Previously, we observed that age alters the balance of destructive (M1) and protective (M2) macrophages, however, the age-related pathophysiology in SCI is poorly understood. NADPH oxidase (NOX) contributes to reactive oxygen species (ROS)-mediated damage and macrophage activation in neurotrauma. Further, NOX/ROS increase with CNS age. Here, we found significantly higher ROS generation in 14 vs. 4-month-old (MO) mice after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 58 publications
6
83
0
Order By: Relevance
“…It is also suggested that the level of microglial NADPH oxidase activity is a major regulator of the shift between M1/proinflammatory and M2/immunoregulatory microglial phenotypes . Zhang et al reported that aging significantly increased NADPH oxidase activation and reactive oxygen species production in Arg1‐positive M2 microglia/macrophages, thereby further increasing age‐related, macrophage‐mediated spinal cord injury secondary tissue damage . Another study by Kumar et al demonstrated that aged mice had increased microglia/macrophage expression of major histocompatibility complex II and NADPH oxidase, and reduced antioxidant enzyme expression which was associated with worse outcome in traumatic brain injury …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also suggested that the level of microglial NADPH oxidase activity is a major regulator of the shift between M1/proinflammatory and M2/immunoregulatory microglial phenotypes . Zhang et al reported that aging significantly increased NADPH oxidase activation and reactive oxygen species production in Arg1‐positive M2 microglia/macrophages, thereby further increasing age‐related, macrophage‐mediated spinal cord injury secondary tissue damage . Another study by Kumar et al demonstrated that aged mice had increased microglia/macrophage expression of major histocompatibility complex II and NADPH oxidase, and reduced antioxidant enzyme expression which was associated with worse outcome in traumatic brain injury …”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence now supports M1/M2 microglia/macrophage polarization alters in several types of acute CNS injuries, including traumatic brain injury, spinal cord injury, and stroke . Aging is suggested to alter the balance between destructive M1 and protective M2 phenotypes, thus contributed to enhanced neuroinflammation and tissue damage following CNS injuries . However, the effect of age on brain microglial polarization in response to peripheral surgical intervention is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For surface receptors (CD86, CD206, Marco) the total threshold area was determined for the entire lesion epicenter then normalized to the threshold area for TomL. Previously we established that TomL specifically labels macrophages within the spinal cord lesion epicenter46 and there was no effect of AZM treatment on TomL density at either time point (p > 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the irreversible property of the primary injury, scientists focus on exploring strategies to reduce secondary injury to adjacent tissues, in order to improve outcome of SCI treatments [4]. Oxidative stress is critical for pathophysiology of secondary damage [5]. In the cell membranes of the CNS, there are a great amount of lipids which are easily vulnerable to free radical.…”
Section: Introductionmentioning
confidence: 99%